PERSONALITY FACTORS THAT HAVE MAJOR CONTRIBUTION TO SECOND LANGUAGE LEARNING - Zafar Qurbonboyev (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Foreign language learning is the process that is contributed by a number of factors such as motivation, interaction, age, personality, learning styles and so on. This phenomenon varies in each person as learners have different understanding and personality.This paper focuses on personality factor in language learning and highlight some personality traits which can play a crucial role in language learning.